Habitat heterogeneity in the assemblages and shell use by the most abundant hermit crabs (Anomura: Diogenidae and Paguridae): does the occupied shell species differ according to gender and species? - Stanski, Gilson; L. Mantelatto, Fernando; Leão Castilho, Antonio (Sociedade Brasileira de Carcinologia, 2016)
Abstract The goal of this study was to identify patterns of shell occupation by different species of hermit crabs from the southern Brazilian coast. In total, 644 individuals were collected, represented by six hermit species. Isocheles sawayai Forest & Saint Laurent, 1968 showed the highest abundance, with 575 individuals, followed by Loxopagurus loxochelis (Moreira, 1901) (n = 56). The other species were Petrochirus diogenes (Linnaeus, 1758), Dardanus insignis (Saussure, 1858), Pagurus exilis (Benedict, 1892) and Pagurus leptonyx Forest & Saint Laurent, 1968. Loxopagurus loxochelis was found associated with shells of 12 gastropod species, with 75% of males occupying shells of Olivancilaria urceus (Roding, 1798) and 78% of females inhabiting shells of Semicassis granulata (Born, 1778). Shells of Semicassis granulata were the lightest of all gastropod shells, demonstrating differential resource utilization. Additionally, I. sawayai occupied shells of 10 species, highlighting Stramonita haemastoma (Linnaeus, 1767) with the highest occupation percentage in all demographic classes, confirming a pattern of occupation with a strong relationship to the availability of the resource. The comparison of our results with those of other studies corroborated the influence of region and gastropod diversity on gastropod shell occupation.
Keywords: Environmental resource; fitness; sexual selection